The Security Role of Football Stadiums on Marketing Mix Development - Zhaleh Memari; Marzieh Lal Bidari; Mahsa Saadati (New Approaches in Sport Sciences, 2020)
The sports industry is one of the most popular fields between the nations that need to interact with several factors, from stadium security to marketing staff. Today, security and crowd management are more critical than ever. In many events, the lack of proper security management has caused to be a bitter event due to it. It has created serious risks for the investors that have participated in the game. Due to this, maintaining a long-term relationship with them is a severe challenge. Research has shown a positive correlation between security in sporting events and security in the business. However, few studies have examined how this is. This study utilized samples that included 300 sport management experts. The research tool included: "Marketing mix standard" and "researcher-made security" questionnaires, each with 45 items. Using exploratory factor analysis, security determinants related to the marketing mix of sports events, which were related to the marketing mix of the tournament, were identified. The results showed that 12 factors have contributed to security, and 11 elements were involved in the marketing mix. The results showed that security documentation and training should receive special attention along with hardware and software management of venues, management and planning, and physical protection, as well as security services and facilities, to improve the security conditions in soccer matches. Managers must have proper management, which leads to the satisfaction of spectators and prevention of crowded. The sense of security creates a suitable atmosphere for marketing activities in sports events.